Effect of Distraction Therapy (Visual) to Pain Response in Children 3-12 Year during IV Line Prosedure at Emergency Ward Piru General Hospital, Western Seram 2017. - Aulia Deby; Aulia Deby Pelu (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Abstract four line procedure is an intervention due to pain for children who hospitalized and causing afraid, anxiety and decreased of children cooperative to do some procedure (Irzan, 2012). This research to know effect of distraction therapy (visual) to pain response in children 3-12 years during IV line procedure. Data has collected on august to September in 2017. This research is quasi experimental that is give intervention to cases group such as visual therapy distraction in IV line procedure in children who with pain response. Population of research in children patient who hospitalized and accept IV line procedure. Sample of this research amounted 10 respondent to intervention group and 10 respondent to control group. The Instrument used pain assessment tool for children: faces pain rating scale from Wong & Baker 2013. Data analysis use Mann-Whitney to know different of paint scale between intervention and control group. Result showed that there was average different of pain scale with significant value p